The plankton of a large oligotrophic fresh-water Antarctic lake - J Laybourn-Parry; HJ Marchant; PE Brown (1991)
The planktonic community of Crooked Lake, a large freshwater lake in the Vestfold Hills, Antarctica was investigated during the austral summer in 1990. Very low levels of chlorophyll a ranging between mean values of 0 29 and 1.8 μl-1 were recorded. The phytoplankton was largely made up of coloured flagellates, including single species of Chlamydomonas, Ochromonas and Pendimum, which occurred in low concentrations (23.8× 102-47.3 ×102 l-1). Heterotrophic colourless flagellates, including Paraphysomonas vestita, were also relatively sparse (2.1× 102-21.3×102 l-1). Ciliated protozoans were particularly poorly represented. Only three species occurred reaching densities of ∼1001-1, and among them the mixotrophic species Strombidium vinde was the most common. A single species of heliozoan Actinosphaerium and relatively large numbers of naked amoebae were the sarcodine representatives The protistan community and the bacteria were concentrated into microbial consortia associated with floes of paniculate organic matter probably derived from the benthic algal mat. Of the two microcrustacean zooplankters recorded from the lake only Daphniopsis studeri was found breeding in the plankton in very low numbers. The behavioural and physiological adaptations of the organisms inhabiting this extremely oligotrophic environment are discussed. © 1991 Oxford University Press.